Evaluation of dual pathogen recognition receptor agonists as adjuvants for respiratory syncytial virus - virus-like particles for pulmonary delivery - Mandviwala, Ahmedali S.; Liman, Komal; Huckriede, Anke L. W.; Arankalle, Vidya A.; Patil, Harshad P. (Frontiers in Immunology, 2025)
IntroductionRespiratory syncytial virus (RSV) remains a significant global health concern, particularly for infants and young children in developing countries. Despite ongoing research efforts, an effective RSV vaccine has yet to be approved for widespread use. Use of two separate pattern recognition receptor (PRR) agonists as adjuvants in vaccine formulations has shown to enhance the immune response against the antigen. The limitation with the use of two adjuvants is that they need not necessarily bind to PRRs on the same cell. This study evaluates the efficacy of two different dual PRR binding chimeric molecules CL413 (TLR2/TLR7 agonist) and CL429 (TLR2/NOD2 agonist) as adjuvants for RSV virus-like particles (VLPs) delivered via the pulmonary route in mice for induction of mucosal and systemic immunity.MethodsBALB/c mice were immunized twice with the RSV-VLPs alone or adjuvanted with CL413, CL429, mixture of single PRR agonists Pam3CSK4+ L18-MDP or Pam3CSK4+ imiquimod via the pulmonary route. The mixture of single PRR agonists adjuvants was used as control for chimeric adjuvants. Immune responses were evaluated by measuring antibody levels in sera and respiratory tract; cytokine production, B and T cell responses in the lungs and spleen.ResultsPulmonary immunization with CL413-adjuvanted VLPs induced robust nasal IgA responses against the RSV F and G proteins, which was not observed for the other adjuvant combinations. CL413 also enhanced serum IgG levels and promoted a balanced Th1/Th2 response, as evidenced by IgG2a/IgG1 ratios. CL413 elicited strong pro-inflammatory responses in the lungs of mice, including elevated levels of IFN-γ, TNF-α, IL-6, and IL-17A. Flow cytometry analysis revealed increased numbers of tissue-resident class-switched B cells in the lungs of mice that were immunized with VLPs adjuvanted with CL413 and CL429. CD4+ and CD8+ T cell responses were also enhanced in both lungs and spleens of mice receiving VLPs adjuvanted with chimeric molecules to various extents. Mice immunized with formalin inactivated RSV (FI-RSV), which are used as the positive control for vaccine induced pathology after RSV challenge developed alveolitis, perivascular infiltration. While all the mice receiving adjuvanted VLP formulations showed protection against lung pathology after RSV challenge.DiscussionThe lack of pathology, combined with the robust mucosal and systemic immune responses, suggests that pulmonary delivery of adjuvanted RSV-VLPs may provide effective protection without the risk of vaccine-enhanced disease. The study also demonstrates that the chimeric TLR2/TLR7 agonist CL413 is a promising adjuvant for RSV-VLPs to induce mucosal and systemic immune response and warrant further investigations in more advanced preclinical models.